PELATIHAN ANALISIS BIBLIOMETRIK MENGGUNAKAN VOSVIEWER DALAM PENINGKATAN KUALITAS DAN KUANTITAS RISET DOSEN DAN MAHASISWA - Putra, Purnama; Basri, Hasan; Nurhidayah, Siti; Khoiriyah, Ummi; Desty Widyowati, Dian; Putrianika, Puput (DEVOSI, 2024)
Bibliometriks is a method of quantitatively analyzing scientific literature to identify publication patterns, authors, and keywords relevant to a field of research. The VOSviewer tool helps in mapping collaboration networks, identifying research trends, and evaluating the impact of scientific work. Analysis of problems related to bibliometrik analysis studies has never been maximized by lecturers and students of Universitas Islam 45. This problem is due to the lack of information, understanding, and clinical skills about analysis applications using VOSviewer. The service method applies the method of training and community assistance through the delivery of question and answer material and discussion as well as implementation practices with assistance. The results of the bibliometrik training service are increased knowledge, motivation and research interest of lecturers and students in competing and interacting with other research at the global and even international levels. Bibliometrik training can also inspire new research ideas and encourage collaboration between researchers. Bibliometrik training equipped with attractive visualizations can contribute to improving the quality of research and strengthening the position of Universitas Islam 45 as an active institution in producing quality scientific work.